1999
DOI: 10.1021/la9809022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Structural Fe Oxidation State on the Coupling of Interlayer Water and Structural Si−O Stretching Vibrations in Montmorillonite

Abstract: The reduction of structural Fe affects many surface chemical properties of smectite clay minerals, including their hydration and interfacial forces. To expand our knowledge of these processes, Fourier transform infrared (FTIR) spectroscopy was used to investigate the effects of structural Fe oxidation state and hydration on layer Si−O stretching vibrations in montmorillonite. Aqueous gels of unaltered, reduced, and reoxidized smectites were equilibrated at different water contents, m w/m c, and swelling pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 68 publications
5
51
0
Order By: Relevance
“…This evidence is consistent with earlier reports of an epitaxial relationship between H20 and clay surfaces Low, 1972, 1977), and that clay surfaces hydrate directly (Low and Margheim, 1980;Low, 1987). The oxidation state of structural Fe in the clay also influences the coupling between interlayer H20 and structural Si-O bands (Yan and Stucki, 1999). This coupling would be inconceivable if H20 is repelled by the clay surfaces or only hydrates the interlayer cation.…”
Section: Introductionsupporting
confidence: 91%
“…This evidence is consistent with earlier reports of an epitaxial relationship between H20 and clay surfaces Low, 1972, 1977), and that clay surfaces hydrate directly (Low and Margheim, 1980;Low, 1987). The oxidation state of structural Fe in the clay also influences the coupling between interlayer H20 and structural Si-O bands (Yan and Stucki, 1999). This coupling would be inconceivable if H20 is repelled by the clay surfaces or only hydrates the interlayer cation.…”
Section: Introductionsupporting
confidence: 91%
“…Iron(II) contents of and 5CA reaction rates with .=-6 smectites Upton, SWa-1, and NG-1 in the unaltered (U), re-E duced (R), and reduced-reoxidized (RR) forms, kob , is the 5CA adsorption-rate constant (rain t); k,, the 4CE formation • rate (min 1); and kob s --kii (min 1), the estimated lifetime of ~ 4 the precursor complex. (Yan and Stucki, 1999). The reduction of structural Fe also increases the surface-charge density of the clay (Stucki, 1988;Stucki and Tessier, 1991;Gates et al, 1993;Yan and Stucki, 1999), causing the Fe(II)-bearing smectites to acquire a strong nucleophilic character that facilitates the transformation of chlorinated alkanes.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of structural Fe also increases the surface-charge density of the clay (Stucki, 1988;Stucki and Tessier, 1991;Gates et al, 1993;Yan and Stucki, 1999), causing the Fe(II)-bearing smectites to acquire a strong nucleophilic character that facilitates the transformation of chlorinated alkanes. The high concentration of H20 relative to that of 5CA, and the fact that smectite surfaces hydrate (Yan et al, 10 ...... 1996b, 1996cYan and Stucki, 1999), suggest that H20 molecules mediate the hydrogen bridging and the long-range interactions between 5CA and the clay surface ("outer sphere complex"; Wilkins, 1991). The formation of tetrachloroethene (4CE) is explained by the dehydrochlorination of 5CA (Roberts and Gschwend, 1991;Cervini-Silva et al, unpubl.…”
Section: Resultsmentioning
confidence: 99%
“…2). This incomplete reversibility of the Fe II ↔ Fe III process was more obvious for low Fe-containing Upton montmorillonite (33). The reductive transformation and sorption of organic molecules are largely determined by the reduction state of the structural Fe.…”
Section: Resultsmentioning
confidence: 98%
“…Previous research found that surface-sensitive properties of smectites including surface charge (49,50), specific surface area (51), interlayer spacing (52), and the structure of interlayer water (29,33,53,54) are significantly modified in the reduced state. The increase of the surface charge density (49) and the decrease of the specific surface area (51) in reduced smectites resulted in a decreased accessibility of interlayer spaces and thus a lower sorption capacity in the reduced smectites for aniline (Fig.…”
Section: Interfacial Interactionsmentioning
confidence: 99%